Oral Health in Veterans Affairs Patients Diagnosed with Serious Mental Illness - Amy M. Kilbourne, PhD, MPH; Marcela Horvitz-Lennon, MD; Edward P. Post, MD, PhD; (Blackwell Synergy, 2007)
We evaluated patient and medication treatment factors associated with self-reported oral health status in patients diagnosed with serious mental illness (SMI) in a large, national sample of patients in the Veterans Affairs (VA) health system.